Industrialization Strategy and the Sustainable Development in Indonesia - Fachru Norfian (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
Even though industrial production in Indonesia has been influenced by the long process of regime changes that increase industrial production from the period of 1971 to the one of 2005, but it has not triggered yet the process of industrialization and so development in Indonesia have not changed significantly despite of its high growth rate for long period notably between 1971 and 1997. In order to verify this hypothesis, this study uses input-output analysis approach that directly tackle sustainable development strategy and sectoral interactions that can detail and reveal structural change and innovation, information that is not provided by other methods. The result is extended with the structural decomposition. The analysis shows that Indonesia has experienced a significant sectors growth during the period while the impact of import substitution and export promotion to the industrialization process was very weak. It is observable that the small and medium enterprises could play a significant role in contributing to the effectiveness of industrialization strategy implementation.